2022
DOI: 10.3389/fphar.2022.828920
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Tibetan Medicine Twenty-Five Wei’er Tea Pills Ameliorate Rheumatoid Arthritis Based on Chemical Crosstalk Between Gut Microbiota and the Host

Abstract: Twenty-Five Wei’er Tea Pills (TFP), a traditional Tibetan medicine, has shown to have a promising therapeutic effect in patients with Rheumatoid arthritis (RA), as well as being safe. Nonetheless, there have been limited pharmacological studies that have explored this therapeutic option. As gut microbiota has been proven to have a critical role in the pathogenesis of RA, this study aims to explore and reveal relevant ways by which TFP interacts with the chemical crosstalk between the gut microbiome and its hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…At the same time, compared with the CON group, the species abundance of Prevotellaceae in the HH group was signi cantly reduced, suggesting that high humidity intervention reduced the abundance of Prevotellaceae in healthy rats. Previous animal experimental studies have shown that the abundance of Prevotellaceae decreased during the immune attack stage of CIA [41], which is consistent with our results. We speculate that high humidity may cause a certain degree of immune response, which may be related to RA.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, compared with the CON group, the species abundance of Prevotellaceae in the HH group was signi cantly reduced, suggesting that high humidity intervention reduced the abundance of Prevotellaceae in healthy rats. Previous animal experimental studies have shown that the abundance of Prevotellaceae decreased during the immune attack stage of CIA [41], which is consistent with our results. We speculate that high humidity may cause a certain degree of immune response, which may be related to RA.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, G-1-P is a common key metabolite involved in multiple metabolic pathways, including starch and sucrose metabolism, amino sugar and nucleotide sugar metabolism, and galactose metabolism. Among them, the dysfunction of amino sugar and nucleotide sugar metabolism has been reported in individuals with various metabolic diseases, such as dyslipidemia, type 2 diabetes, and NAFLD ( Huang et al, 2020 ; Li et al, 2022b ). However, evidence to clarify the relationship between the metabolic pathway and NAFLD in previous studies is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics tools that are constantly updated provide new insights for drug development through high-throughput screening, targets prediction, and pathways enrichment. Traditional Chinese herbs have shown to be effective in treating joint disorders such as OA, RA [ 24 ], and gouty arthritis [ 25 ]; however, the key ingredients responsible for their therapeutic effects and underlying mechanisms by which their effects are manifested are still unknown. According to our bioinformatics results, Ginkgo biloba may exert anti-arthritic effects by inhibiting inflammatory cytokines such as IL-6 and modulating oxidative stress proteins such as hypoxia-inducible factor 1 subunit alpha (HIF-1α) and nuclear factor erythroid 2-related factor 2 (NFE2L2, NRF2).…”
Section: Discussionmentioning
confidence: 99%